2020
DOI: 10.1177/0974910119896634
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Alliance and Its Influence on the Performance of Small- and Medium-scale Enterprises in Enugu State, Nigeria

Abstract: Small- and medium-scale enterprises (SMEs) are the engine of economic growth and equitable development in emerging economies such as Nigeria. Their role in emerging market development can be seen in the areas of capital saving, utilization of local resources, and job creation among others. Enugu State is one of the emerging industrial hubs in Nigeria with SME base of 1,366. The activities of these enterprises have significantly increased the revenue base of the government, making the area an emerging market ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 24 publications
(36 reference statements)
0
18
0
Order By: Relevance
“…It lies between the Equator's latitudes of 5 0 58 1N and 7 0 081N, and the Greenwich Meridian's longitudes of 7 0 081E and 7 0 481E as was shown in as seen in Figures 1. The area is made up of seventeen (17) Local Government Areas as was described elsewhere in Nwokocha (2020). The research area is home to a plethora of industrial activities.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…It lies between the Equator's latitudes of 5 0 58 1N and 7 0 081N, and the Greenwich Meridian's longitudes of 7 0 081E and 7 0 481E as was shown in as seen in Figures 1. The area is made up of seventeen (17) Local Government Areas as was described elsewhere in Nwokocha (2020). The research area is home to a plethora of industrial activities.…”
Section: Study Areamentioning
confidence: 99%
“…In addition, the State's SME directory revealed that there are one thousand three hundred and sixty-six (1,366) such industries in the selected LGAs. Because data on Industries in other LGAs were unavailable, the choice to focus on the 12 (twelve) LGAs was made as was explained elsewhere in Nwokocha (2020). In the study area, seven (7) industrial groups yielded a total of 1,366 registered industries.…”
Section: Sample Selection and Sample Sizementioning
confidence: 99%
“…According to Yang and Meyer (2019), alliance proactiveness indeed interacts with both capabilities and market growth; probably most interesting is the finding that the combination of alliance proactiveness with technological capabilities and market growth has the highest impact on firm performance. The work of Nwokocha and Madu (2020) found that strategic alliance cumulatively led to an increase in the performance of SMEs in Nigeria. The study showed that strategic alliance lead to 0.55 unit increase in sales growth, 0.58 unit increase in growth in market share and 0.56 unit increase in product success.…”
Section: Literature and Theoretical Frameworkmentioning
confidence: 99%
“…This study was carried out in 12 Local Government Areas (LGAs) of Enugu State as was explained elsewhere in Nwokocha and Madu (2020). A total of one thousand three hundred and sixty six (1,366) SMES were identified from seven (7) industrial groups in the study area after a preliminary field work was carried out to update the existing industrial directory obtained from Enugu State SME directory.…”
Section: Sample Selection and Sizementioning
confidence: 99%
See 1 more Smart Citation